Additional considerations before using a ctDNA-guided approach for informing adjuvant chemotherapy in colorectal cancer - Timothée Olivier; Alyson Haslam; Vinay Prasad (BMC Medicine, 2023)
Abstract Background The DYNAMIC trial investigated the use of circulating tumor DNA (ctDNA) to guide adjuvant treatment decisions in stage II colon cancer. Despite the DYNAMIC trial’s assertion that a ctDNA-guided approach could minimize the use of adjuvant treatment without compromising recurrence-free survival (RFS), we raised concerns regarding the trial’s methodology and the practical implications of its findings in a Debate article. Here, we expand upon these concerns in a response to a correspondence by the authors of the DYNAMIC trial. Main body We dispute the choice of a large non-inferiority margin in the DYNAMIC trial, simply because an 8.5 percentage points decrease in recurrence-free survival could result in significant harm to patients. We challenge the authors’ comparisons of the DYNAMIC trial outcomes with observational studies. Such comparison is subject to selection bias and changes over time that limit their relevance. The prognostic role of ctDNA do not automatically imply that more treatment in patients with ctDNA positivity would improve outcomes, which we highlight. In real-world settings, we anticipate a potential rise in chemotherapy use due to clinicians utilizing ctDNA alongside existing clinicopathologic factors, rather than using ctDNA as an entire replacement. Lastly, a key concern in DYNAMIC was an 350% higher use of oxaliplatin in the ctDNA arm compared with standard management (9.5% versus 2.7%, respectively), which poses a risk for long-term neuropathy. Conclusion We look forward improvements in patient selection in the adjuvant setting, but we maintain our reservations about the DYNAMIC trial and the real-life implementation of its results. As an alternative to exploring de-escalation strategies with large margins non-inferiority trials, we propose that superiority trials in stage II patients could be a more effective strategy.